Classification and Grading of Central Nervous System Tumors According to the World Health Organization 5th Edition - Yoda, Rebecca A.; Cimino, Patrick J. (Seminars in Neurology, 2023)
The World Health Organization (WHO) released the 5th edition of its classification of central nervous system (CNS) tumors in 2021. Advances in the landscape of molecular tumor pathophysiology prompted major revisions to the previous edition released in 2016, some of which were first introduced by the Consortium to Inform Molecular and Practical Approaches to CNS Tumor Taxonomy—Not Official WHO (cIMPACT-NOW). The 2021 classification system integrates newly gained molecular insights to guide changes in tumor taxonomy and nomenclature, introduces several new types of tumors, and expands the use of molecular testing for diagnosis and grading, with a particular impact on adult-type and pediatric-type gliomas, ependymomas, and embryonal tumors. These updates aim to promote clear and accurate diagnoses, yield more reliable prognostic information, and enable the selection of optimal therapies. Familiarity with these changes will be of great importance for clinicians involved in the management of CNS tumor patients.
Keywords: central nervous system; World Health Organization; neuropathology; brain tumor; classification